PERSONALIZED LEARNING IN THE AVIATION INDUSTRY: DEVELOPMENT OF AIRPORT AND HELIPORT TEACHING MATERIALS BASED ON BLENDED LEARNING - Irfan, Irfan; Suhanto, Suhanto; Jaya, Irwan; Sukarwoto, Sukarwoto (Universitas Labuhanbatu, 2025)
Purpose – Blended Learning in the Aerodrome & Heliport course combines theory and practice flexibly and interactively. Conventional methods are less effective due to the lack of active involvement and limited access to learning materials. This study aims to develop blended learning-based learning materials to improve student competency in the Aerodrome & Heliport course at the Makassar Aviation Polytechnic. In addition, this study was conducted due to the low academic achievement of students, with 20% failing the course.Methodology – The research used the Research and Development (R&D) model. However, only the first three stages are worked on: define, design, and develop. This research involves 24 air transport management diploma program students as respondents and two radio aids to air navigation instructor respondents. Data were collected through survey, interview, observation, and documentation. Assessments from experts on blended Learning and aviation education using qualitative and quantitative analysis methods were conducted to assess the validity of the developed teaching materials.Findings – The study demonstrated that blended Learning considerably raised student proficiency. The methodically created instructional materials received a high validity grade from specialists who rated them as